2007
DOI: 10.4049/jimmunol.178.5.3281
|View full text |Cite
|
Sign up to set email alerts
|

Aberrant Expression of the Insulin-Like Growth Factor-1 Receptor by T Cells from Patients with Graves’ Disease May Carry Functional Consequences for Disease Pathogenesis

Abstract: Graves’ disease (GD), an autoimmune process involving thyroid and orbital tissue, is associated with lymphocyte abnormalities including expansion of memory T cells. Insulin-like growth factor receptor-1 (IGF-1R)-bearing fibroblasts overpopulate connective tissues in GD. IGF-1R on fibroblasts, when ligated with IgGs from these patients, results in the expression of the T cell chemoattractants, IL-16 and RANTES. We now report that a disproportionately large fraction of peripheral blood T cells express IGF-1R (CD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
98
0
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 130 publications
(106 citation statements)
references
References 67 publications
(72 reference statements)
7
98
0
1
Order By: Relevance
“…Douglas et al (2009) found that the majority of clinically healthy, unaffected monozygotic twins in discordant pairs failed to exhibit an IGF-IR ϩ skewed population of circulating T and B cells compared with their twin with Graves' disease. The study replicated observations made earlier by the same authors in a separate North American cohort of patients with sporadic Graves' disease (Douglas et al, 2007. It is noteworthy that this recent study demonstrates that the more frequent display of IGF-IR on T and B cells, associated with Graves' disease, seems to derive from acquired rather than genetic factors.…”
Section: Cd45rosupporting
confidence: 89%
See 2 more Smart Citations
“…Douglas et al (2009) found that the majority of clinically healthy, unaffected monozygotic twins in discordant pairs failed to exhibit an IGF-IR ϩ skewed population of circulating T and B cells compared with their twin with Graves' disease. The study replicated observations made earlier by the same authors in a separate North American cohort of patients with sporadic Graves' disease (Douglas et al, 2007. It is noteworthy that this recent study demonstrates that the more frequent display of IGF-IR on T and B cells, associated with Graves' disease, seems to derive from acquired rather than genetic factors.…”
Section: Cd45rosupporting
confidence: 89%
“…Unlike TAOderived orbital fibroblasts, in which cell-surface IGF-IR densities are 3-to 4-fold higher than those on control cells, receptor levels on T cells from patients with Graves' disease are similar to those found on control lymphocytes (Douglas et al, 2007). As with fibroblasts, T cells bearing the IGF-IR ϩ phenotype exhibit preferential resistance to apoptosis and a growth advantage in vitro.…”
Section: Cd45romentioning
confidence: 83%
See 1 more Smart Citation
“…They were washed, resuspended in staining buffer at 4°C, and subjected to FACS analysis in a Calibur flow cytometer (BD). For intracellular Tg staining, cells were permeabilized as reported (39). Mean fluorescent intensity is the ratio of mean fluorescence sample:isotype control fluorescence.…”
Section: Methodsmentioning
confidence: 99%
“…Overrepresentation of IGF-IR-expressing lymphocytes has recently been described. T cells isolated from orbital connective tissue and those circulating in peripheral blood of patients with GD demonstrate increased IGF-IR display (7). The IGF-IR ϩ phenotype is found in a disproportionate fraction of CD45RO ϩ (memory) CD4 ϩ , and memory CD8 ϩ T cells.…”
mentioning
confidence: 99%